Elementary calculus - Durell, Clement V.; Robson, A. (London : G. Bell and Sons; Ltd., 1966)
Volume One forms an introduction to the subject designed to meet the needs of the ordinary student and is suitable also, as a preliminary course, for those who may afterwards become mathematical specialists. It includes all that is necessary for what is usually known as "additional mathematics'' or mathematics "more advanced'' in school certificate and matriculation examinations. Also special attention has been given to the construction of the exercises; these are sufficient to illustrate all the elementary applications, but they are no longer than is necessary for this purpose.
ne 19/03/2018
Loans
Keywords: Calculus